The Effect of Family Empowerment in Nursing Implementation Toward Self-Efficacy among Patients with Diabetes Mellitus - Fadhil Al Mahdi; Candra Kusuma Negara; Abd Basid (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introduction: : Diabetes mellitus is a condition where the body cannot produce the insulin hormone as needed so that there is an excess of normal blood sugar levels. Giving family empowerment in clients with gangrene foot diabetes should be done comprehensively using the nursing process. Interventions that can be done are family empowerment to motivate and improve the self-efficacy of patients with diabetes mellitus. The purpose of this study was to determine the effect self-efficacy before and after the implementation of family empowerment in nursing in patients with diabetes mellitus. Methods: Pre-experiment research with pretest and posttest study design without control group. Forty respondents who met the inclusion criteria were then tested using purposive sampling. The instrument in this study used a self-efficacy questionnaire. The dependent variable of this study is self-efficacy, while the independent variable is family empowerment using the paired sample t-test parametric analysis method. Results: Based on what was answered by the respondents there was a significant influence which showed difference after the posttest. The results obtained values: α = 0.05 which calculated the results of p = 0.00 (p <0.05). This means that, after a posttest, there was a decrease in motivation and self-efficacy. Conclusion: Researchers concluded that there is an effect of family empowerment on patients with diabetes mellitus. The implication of this study is that the role of family is very important in healing patients.